PERILAKU SUPERVISI PENDIDIKAN - Nufus, Hayatun; Rahmawati, Ima; ihsan, Muzhir Ihsan (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
This article discusses the behavior of educational supervision carried out by educational supervisors such as school principals, administrators, or mentors. Educational supervision plays a crucial role in ensuring optimal education quality. The attitudes and behaviors of supervisors influence the effectiveness of educational supervision and the professional development of teachers. This study identifies the main characteristics that educational supervisors should possess, including corrective, preventive, constructive, creative, and cooperative attitudes. Additionally, this paper reviews the types of behaviors in educational supervision, namely directive, collaborative, and non-directive behaviors. A deeper understanding of supervisors' attitudes and behaviors is expected to help identify best practices, overcome obstacles, and find opportunities to improve the effectiveness of educational supervision, as well as motivate teachers to enhance the quality of learning and create a work environment that supports professional development.